A Novel Technique for Femoral Stem Extraction Through the Direct Anterior Approach: The Medial Episiotomy With Anterior Transfemoral Osteotomy - Brian Omslaer, DO; Shaan Sadhwani, DO; Jamie Henzes, DO; Steven Deluca, DO; Muzaffar Ali, DO (Arthroplasty Today)
This report describes a medial calcar episiotomy with partial anterior transfemoral osteotomy of the proximal femur to aid in removal of a femoral component in setting of revision total hip arthroplasty through a direct anterior approach. Revision total hip arthroplasty is challenging, labor-intensive, and carries high complication rates. Previously described techniques such as extended trochanteric osteotomies can be utilized to facilitate removal of fixed femoral stems. The technique herein described was performed in an effort to avoid the morbidity of additional dissection and risk of nonunion associated with complete osteotomy of the trochanteric region. We present a novel technique to aid in the removal of a fixed femoral stem in the setting of revision total hip arthroplasty through an anterior approach. This technique has not previously been described specifically in the literature and was performed safely and effectively for this patient. A complication-free outcome with osteotomy union was achieved on a final follow-up of 13 months.